INVENTORY OF PLANTS THAT PROVIDE NON-WOODY FOREST PRODUCTS IN A MIXED-ARAUCARIA FOREST IN PARANA STATE, BRAZIL - SANQUETTA, Carlos Roberto; FERNANDES, Lucila de Almeida Vasques; MIRANDA, Dirceu Lúcio Carneiro de; MOGNON, Francelo (Scientia Agraria, 2010)
The Araucaria Forest was intensively exploited in the past, in the part for timber and firewood extraction from the forest. Currently environmental legislation restricts and in many cases prohibits the cutting of forest wood, making it often a problem for landowners who eventually chose illegal extraction. The study objective was to identify and quantify the non-wood forests species of a fragment of Araucaria Forest. The study was carried out in a fragment of Araucaria Forest in São João do Triunfo, Brazil, where the species with terrestrial and epiphytic habit were taken into account. The inventory of the tree species was conducted through the use of 350 plots of 100 m² and the inventory of other species was conducted through the use of 128 plots of 4 m². The phytosociological analysis was performed and a review of literature was performed with the purpose of verifying the potential uses of non-wood forests species surveyed. The results indicated the presence of 884 trees.ha-1, with the identification of 71 species. Of these, 61.97% had possible non-wood uses. As those not trees, the inventory showed 15,371 individuals.ha-1 with terrestrial habit and 4,063 epiphytes per ha, with the identification of 63 species, of which 44.44% can provide non-wood forests products. It can be concluded that the fragment studied had a large number of species and these can provide multiple uses for landowners, minimizing the illegal exploitation of wood, may be an economically viable alternative, environmentally correct, directing the property to the sustainable management.